Strategi Dakwah Yayasan Jember Berbagi Berkah Bersama di Wilayah Jember - Muhammad Nur Khafi; Ahidul Asror (Maddah: Journal of Advanced Da'wah Management Research, 2022)
In the current era, many young people have lost their way, so they need to be invited and embraced to return to the right path by means of da'wah. Example da'wah with actions such as alms is one carried out by the Jember Sharing Berkah Bersama Foundation. The focus the problem: 1) What is the missionary strategy of the Jember Foundation to Share Blessings Together in the Jember area? 2) How is the implementation the missionary program the Jember Sharing Blessings Foundation in the Jember area?. The research objectives: 1) to describe missionary strategy the Jember Sharing Berkah Bersama Foundation in the Jember area. 2) to describe the implementation missionary program Jember Sharing Blessings Together Foundation in the Jember area. The researcher: descriptive qualitative research. Data collection: interviews, documentation, observation. Data analysis: data collection, data condensation, data presentation, conclusion. This Concluded: 1) The Da'wah Strategy of the Jember Foundation for Sharing Blessings Together in the Jember area, namely: a. Managing activities in the social, humanitarian and religious fields through Friday sharing preaching programs, caring for orphanages, caring for pedicab drivers, road repairs, taklim assemblies, 7 boxes mineral water for bereaved families and free rice. b. Helping the Economy of Underprivileged Communities through Friday sharing preaching programs, caring for orphanages, caring for pedicab drivers, productive waqf. c. Empowerment and Potential Development through productive waqf da'wah programs. 2) The implementation program Jember Sharing Blessings Together Foundation in Jember area is divided into three, namely Friday sharing, caring for orphanages and productive waqf.